2012
DOI: 10.1016/j.jada.2011.08.049
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and Sociocultural Influences on Dietary Intake and Health Status among Puerto Rican Adults in Massachusetts

Abstract: Background Previous studies have shown negative consequences of acculturation on lifestyle factors, health status, and dietary intake of Hispanic immigrants in the US. Despite prevalent type 2 diabetes and low socioeconomic status (SES) among Puerto Rican adults living on the US mainland, little is known about acculturation in this group. Objective We investigated associations among acculturation, lifestyle characteristics, health status, and carbohydrate nutrition in Puerto Rican adults. A secondary objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 75 publications
5
42
1
Order By: Relevance
“…This discrepancy may speak to the greater similarities between the island of Puerto Rico and the mainland US than those seen between other countries of origin and the US. Previous research has shown different patterns of dietary acculturation and weight-status among Puerto Ricans and MexicanAmericans (Bates et al, 2008;Van Rompay et al, 2012). Our findings suggest that time in food preparation may be one of the mechanisms underlying these documented dietary differences.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…This discrepancy may speak to the greater similarities between the island of Puerto Rico and the mainland US than those seen between other countries of origin and the US. Previous research has shown different patterns of dietary acculturation and weight-status among Puerto Ricans and MexicanAmericans (Bates et al, 2008;Van Rompay et al, 2012). Our findings suggest that time in food preparation may be one of the mechanisms underlying these documented dietary differences.…”
Section: Discussionmentioning
confidence: 45%
“…It is theorized that the "obesogenic" environment encountered in the US (Giskes, van Lenthe, Avendano-Pabon, & Brug, 2011;Hill, Wyatt, Reed, & Peters, 2003) plays a role in the rising rates of obesity among im/migrant (Tovar et al, 2013). These relationships are not without nuance; dietary quality may improve with acculturation among Puerto Ricans (Van Rompay et al, 2012) for whom some evidence suggests that weight may trend downward over generations on the US mainland (Bates, Acevedo-Garcia, Alegría, & Krieger, 2008), although another study indicates a pattern of weight gain (Himmelgreen et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Another Hispanic-Latino group in whom previous published dietary estimates exist is Puerto Ricans. HCHS/SOL Puerto Ricans, who were mainly from the Bronx, reported lower intakes of total energy, macronutrients, and fiber than did those who were living in the greater Boston area (27). However, differences may have been attributed to the type of methodology used to collect dietary data (ie, 24-h recalls compared with a food-frequency questionnaire).…”
Section: Discussionmentioning
confidence: 99%
“…Puerto Ricans reportedly follow inadequate dietary, physical activity, smoking, and sleep habits (37)(38)(39)(40), and they also present unique patterns of social integration, social and emotional support, and cultural adjustment (41)(42)(43)(44), which may increase their vulnerability for metabolic disorders. Using the AHA recommendations on diet, physical activity, and BMI, Bhupathiraju et al (45) developed a lifestyle score that was associated with lower CVD risk factors in Puerto Rican adults.…”
Section: Introductionmentioning
confidence: 99%